Oralne fundamenty wielkanocnej wiary Kościoła - zarys perspektywy - Piotrowski, Eligiusz (Uniwersytet Wrocławski. Instytut Studiów Klasycznych, Śródziemnomorskich i Orientalnych, 2016)
The resurrection of Jesus of Nazareth is the foundation of the Christian faith. The research into its origins does not only serve the purpose of satisfying human curiosity, but it aims to discover its essence. The texts of the New Testament serve as the foundation of the aster faith and the Christophany. The interpretations of the above realities, relying on the same texts, lead researchers to sometimes completely contradictory conclusions. On the one hand we deal with the historicity and the certainty of the empty tomb; on the other hand with the indication of its legendary character. Then we are dealing with firstly the material certainty of the corporeality of the Risen, and secondly with the subjective and mysterious character of His presence. Throughout this historical process research into the oral lore prior to the record of the biblical text proves to be extremely useful.In this way we may reconstruct the events which gave birth to western civilization.
Keywords: zmartwychwstanie; wskrzeszenie Jezusa; NowyTestament; kerygmat; fakt historyczny; pusty grób; apostoł Paweł